Interprofessional education or silo education? - Brocklebank, Hugh James; Jowsey, Tanisha (Canadian Medical Education Journal, 2019)
Hand drawn and coloured using Adobe Photoshop 2015. This image depicts the difficulties that practitioners have in working in interprofessional teams when they train in separate buildings and don't learn together.